Tabriz dans L’Usage du monde : Un cosmopolitisme dans les marges - Sarga Moussa (Viatica)
This study explores a specific and paradigmatic episode of Nicolas Bouvier’s The Way of the World: the long stopover in the Iranian city of Tabriz given the winter conditions. The analysis focuses on the cosmopolitical and multicultural dimension of Tabriz, but also considers the character of a geographically marginal city, guardian of a way of life which inspires and encourages creativity. Essentially left open to chance encounters, Bouvier experiences the abandonment of self and even unveils a desire for metamorphosis, later to be found in The Scorpion-Fish.